Amplified Bimodal Distribution of Western North Pacific Tropical Cyclone Lifetime Maximum Intensity - Qian Xiang; Haikun Zhao; Philip J. Klotzbach; Tonghua Su; Chao Wang; Liguang Wu (Geophysical Research Letters, 2025)
Abstract The impact of a warming climate on tropical cyclones (TCs) remains unclear. Here, we find that the probability density function for western North Pacific TC lifetime maximum intensity (LMI) has an amplified bimodal distribution in recent years. This change implies a trend toward more extreme TCs and fewer moderate TCs. Changes in the TC LMI distribution are associated with alterations in the occurrence of rapidly intensifying TCs. Changes in TC tracks, due to alterations in the steering flow linked to a weakening Hadley cell, cause more TCs to move northwestward into a more favorable environment for intensification with large ocean heat content. Consequently, more rapidly intensifying TCs reach higher intensities, significantly contributing to the observed amplified bimodal distribution. These findings provide new insights into changes in TC intensity and highlight the increasing threat to coastal areas from more intense TCs in a warming climate.